How dominant coalition members' values and perceptions impact their perceptions of public relations participation in organizational decision making. Issue 3 (1st August 2016) - Wilson, Christopher
Abstract : Purpose: This study seeks to understand the extent to which dominant coalition members' values and perceptions influence their perceptions of public relations participation in organization-level decision making. Research in this area has largely focused on the relationship between practitioner roles and decision-making inclusion. Design/methodology/approach: The population of interest was dominant coalition members of for-profit, government, and nonprofit organizations in the United States. Data were collected through a national survey to a nonrandom sample of 201 dominant coalition members. Findings: Results indicate that dominant coalition members' values of organizational openness to the environment and perceived substantive autonomy of the organization positively predicted perceptions of public relations participation in organizational decision making. Perceived manager role potential of the public relations department also had significant predictive power. Originality/value: While research has focused primarily on the characteristics that public relations practitioners can develop to earn a seat at the management table, little is known about the characteristics of dominant coalition members that influence whether or not a seat is made available or the degree to which public relations is perceived to participate in decision making.